Chiral bay-alkynylated tetraazaperylenes: photophysics and chiroptical properties - Eichelmann, Robert; Jeudy, Pierre; Schneider, Lars; Zerhoch, Jonathan; Mayer, Paula R.; Ballmann, Joachim; Deschler, Felix; Gade, Lutz H. (Universität, 2024)
Fully bay-alkynylated octaazaperopyrene dioxide (OAPPDO) derivatives were accessible through Stille cross coupling reaction of the corresponding bay-chlorinated derivatives. This steric congestion of the bay area led to helically chiral fluorophores, and chiral resolution of two derivatives allowed the investigation of their chiroptical properties as well as their kinetics of enantiomerization and the related thermodynamic parameters depending on the size of the terminal alkynyl substituent. An increase of the latter resulted in stable OAPPDO atropisomers at room temperature. The dynamics of the photoexcited states of two of the OAPPDO derivatives were investigated by transient absorption (TA) and time-resolved photoluminescence (tr-PL) spectroscopy.
Gefördert durch: German Research Foundation: INST40/575-1FUGG (Justus cluster), German Research Foundation: SFB1249 (TP A2)
Gesehen am 28.02.2024
Keywords: Forschungsdaten; Datenbank